TINJAUAN YURIDIS TERHADAP PERLINDUNGAN ANAK DALAM RUANG SIBER DI INDONESIA - Mekar Satria Utama (GEMA, 2023)
This article aims to provide a juridical review of child protection in the cyberspace in Indonesia. The research employs a juridical-empirical method by analyzing the legal framework governing child protection in the cyberspace in Indonesia, involving empirical elements to assess the effectiveness and implementation of child protection policies. The results of this study indicate that the concept of shared responsibility among stakeholders, as applied in Law Number 23 of 2003 concerning Child Protection, serves as a relevant foundation. However, to achieve optimal child protection in cyberspace, the implementation of a holistic multi-aspect approach is required, and collaboration between the government, society, parents, and the private sector is crucial to effectively address and mitigate threats in the cyber world.